Analysis of Human Resource Competencies In Facing The Industry 4.0 Era - Samiun, Samiun; Wijaya, I Ketut Kusuma; Baiq Rabiatul Adawiyah Kartika Wulan (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the competencies of Indonesian human resources (HR) in facing the challenges of the Industry era. The research employed a qualitative approach through in-depth interviews with informants from the industrial sector, vocational education, and training institutions. Findings reveal that HR competencies—both technical (hard skills) such as digital technology proficiency, and non-technical (soft skills) such as critical thinking, adaptability, and initiative—are not yet optimal. Several inhibiting factors in competency development include limited access to training, weak organizational support, and misalignment between education and industry needs. Strategies to address these challenges include continuous training, fostering a learning culture, utilizing online learning technologies, and enhancing collaboration among educational institutions, industries, and the government. This study highlights the importance of an adaptive and responsive learning ecosystem to shape HR capable of navigating technological changes and the dynamic digital work environment.